Should ride-sharing platforms cooperate with car-rental companies? Implications for consumer surplus and driver surplus. (July 2021) - Lin, Xiaogang; Sun, Cuiying; Cao, Bin; Zhou, Yong-Wu; Chen, Chuanying
Highlights: We studied the impact of without-car drivers of a ride sharing platform on consumer surplus and driver surplus. The optimal price and wage for the platform are not necessarily monotonic. A second driver source can lead to a win–win–win outcome. The win–win–win outcome can easily be achieved for a large customer size or delay cost but a small driver size or service rate. Abstract: The booming on-demand ride-sharing economy induces drivers who do or do not own cars to provide services on ride-sharing platforms. To meet growing demand, in practice the platforms have cooperated with car-rental companies that rent cars to without-car drivers to improve their supplies. However, this might harm the platforms, consumers, and drivers, since such a second capacity source may increase customers' waiting time and reduce drivers' utilization. In this paper, we study the impact of without-car drivers in a car-rental company on a ride-sharing platform, consumer surplus, and driver surplus. The platform must decide whether to cooperate with the car-rental company, which entails a per-service price charged to customers and a per-service wage paid to (with-car and without-car) driver. In turn, the car-rental company charges without-car drivers who would like to provide services on the platform a price, and pays a commission rate to the platform. We analyze a stylized model in which customers decide whether to use the platform based on price and expected waiting time, and drivers base decisions about whether to work for the platform on wage and the probability of getting jobs. Driven by these two features, we find that the platform would prefer to cooperate with the car-rental company, and the optimal price and wage (profit) of the platform are not necessarily monotonic (increases) in the potential number of without-car drivers or the commission paid by the company. We also find that when the commission rate is high or the fixed payout ratio is low, cooperation can yield a win–win–win outcome for the platform, customers, and drivers. This provides a plausible explanation of why most ride-sharing platforms would cooperate with car-rental companies in practice. In addition, we find that such a win–win–win outcome can easily be achieved for a large customer size or delay cost but a small (with-car and without-car) driver size or service rate.